GAMBARAN PROSEDUR DAN SISTEM MANAJEMEN INSTALASI GAWAT DARURAT (IGD) DI RUMAH SAKIT JIWA MUTIARA SUKMA PROVINSI NUSA TENGGARA BARAT - Sulistianingsih; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani; Wahyu Aprilyaningsih (Nusadaya Journal of Multidiciplinary Studies, 2025)
Emergency Room is an important component in the health service system in a mental hospital, which handles patients with acute psychiatric conditions. This study aims to describe the procedures and management systems of the Emergency Room at Mutiara Sukma Mental Hospital, West Nusa Tenggara Province in 2025. The study used a qualitative approach with in-depth techniques to three main informants, the Emergency Room Coordinator, Emergency Room and Emergency Room Administration officers. The results of the study indicate that the implementation of the Emergency Room Service procedure has followed the Standard Operating Procedure, supported by a management system based on the Plan-Do-Study-Act method, medical team communication with the S-BAR approach, and administrative management using a combination of Electronic and manual systems. Staff performance evaluations are carried out periodically, and the patient feedback system is the basis for improving the quality of service.